Pengaruh Overtime Dan Insentif Terhadap Produktivitas Pekerja Konstruksi Pada Proyek Pembangunan Rumah Susun Pesisir Barat Lampung - Tungga Buana Irfana; Liston Sitorus (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
This study aims to look at work productivity in order to obtain optimal work results, then efforts to improve work productivity first need to know the factors that affect work productivity with Overtime and Intentive variables as independent variables, the effect of overtime implemented within a certain period will affect the productivity of workers and the influence of incentives is one of the tools to encourage and direct the activities of subordinates to achieve company goals. In this research design using a causal method (cause and effect) and using a quantitative approach. The method used is the multiple linear regression approach using SPSS applications. The results of this study are Over time partially does not have an effect on Productivity, Incentives partially have an influence and significant on Productivity and Over time (X1), and Incentives (X2) together on Productivity (Y).